A theory of ISIS: political violence and the transformation of the global order - Mohamedou, Mohammad-Mahmoud Ould (Pluto Press, 2018)
Presenting a new theory of ISIS, Mohamedou traces its genealogy and documents its evolution in Iraq and Syria. He argues that ISIS has transcended Osama Bin Laden's original project of Al Qaeda, mutating into an unprecedented hybrid form that distills postcolonial violence, postmodernity and the emerging post-globalization international order. Mohamedou analyzes ISIS from a social sciences perspective and unpacks its dynamics by looking beyond superficial questions such as its terrorist nature and religious rhetoric. He transforms our understanding of ISIS and its impact on the very nature of contemporary political violence. --Adapted from publisher description